Dietary patterns acquired in early life are associated with cardiometabolic markers at school age. Issue 7 (July 2021) - Luque, Veronica; Closa-Monasterolo, Ricardo; Grote, Veit; Ambrosini, Gina L.; Zaragoza-Jordana, Marta; Ferré, Natalia; Theurich, Melissa; Koletzko, Berthold; Verduci, Elvira; Gruszfeld, Dariusz; Xhonneux, Annick; Escribano, Joaquin
Summary: Background & aims: it has previously been described that dietary patterns established early in life tracked to late childhood. The aim of the present work was to analyse the association of dietary patterns that tracked from 2 to 8y with cardiometabolic markers at 8y of age. Methods: The 3 identified patterns at 2y (that previous analyses showed to track to age 8y) were: "CoreDP ", loaded for vegetables, fruits, fish, olive oil, etc.; "F&SDP ", loaded by poor-quality fats and sugars; and "ProteinDP ", mainly loaded by animal protein sources. Cardiometabolic markers at 8y were systolic blood pressure (SBP), insulin resistance (HOMA-IR), and triglycerides, and BMI z-score. To examine whether the association of diet with the outcomes was the result of a direct effect of diet at either two or 8y, or synergy between them, we used structural equation models. Results: the associations between the patterns and the health outcomes were: CoreDP was inversely associated with SBP and HOMA-IR; ProteinDP was directly associated with HOMA-IR and SBP; and adherence to F&SDP was directly associated with triglycerides and SBP. The associations between the patterns and the health outcomes were independent of BMI and were the result of a direct effect of diet at 2y, an indirect effect of diet at 2y through diet at 8y or a combination between both pathways. Conclusion: dietary patterns acquired in early life, persisting to later childhood, were associated with cardiometabolic markers at school age independently of BMI.